Predominant Stroma-Rich Feature in Hyaline Vascular Variant of Castleman Disease Is Associated With Paraneoplastic Pemphigus: A 20-Year Retrospective Study of 123 Chinese Patients With Castleman Disease. Issue 3 (27th May 2020) - Wang, Leyi; Nong, Lin; Li, Furong; Wang, Xue; Wang, Rui; Chen, Xixue; Tu, Ping; Dong, Yujun; Li, Ting; Zhu, Xuejun; Wang, Mingyue
Abstract: Objectives: We aimed to describe the clinical and histopathologic features of Castleman disease (CD), particularly emphasizing its associations with paraneoplastic pemphigus (PNP) and prognosis. Methods: We retrospectively enrolled 123 CD patients at our center. Clinical, pathologic, and laboratory data were reviewed. Results: Fifty percent of the patients had PNP. Compared with those without PNP, patients with PNP-associated CD had more hyaline vascular (HV) variants (83.9% vs 57.4%), fewer mixed cellular variants (16.1% vs 24.6%), and no plasmacytic variants (0% vs 18.0%). Thirty-eight of 87 patients with the HV variant of CD (HV-CD) had stroma-rich (SR) features, and the incidence rate was higher in those with PNP-associated CD than in those without PNP (48.4% vs 13.1%, P < .001). The SR variant was associated with higher PNP-associated IgG titers than SR absence before surgery (median 1:160 vs 1:80, P = .019) or after surgery (median 1:160 vs 1:40, P = .013). The SR variant was also an unfavorable prognostic factor for CD survival in univariate analysis. The 3-year survival rates were 47.5% among those with PNP and 87.7% among those without PNP ( P < .001). Conclusions: PNP is associated with specific subtypes of CD and affects survival. The SR variant of HV-CD positively correlates with the incidence of PNP.